Effects on postgraduate-year-I residents of simulation-based learning compared to traditional lecture-style education led by postgraduate-year-II residents: a pilot study - Yamamoto, Akira (BMC Med Educ, 2019)
BACKGROUND: Simulation-based learning plays an important role in contemporary medical education, although there are problems providing tutors. Peer-assisted learning has begun being formally adopted in medical education. Although it is considered useful for simulation-based learning, its effectiveness remains unclear. This study was designed to compare the effect of simulation-based learning with that of traditional lectures conducted by postgraduate-year (PGY)-II residents on PGY-I residents. METHODS: This study was conducted at Okayama University Hospital over three years, for one week each year, before residents entered clinical practice. The study enrolled 76 PGY-I residents, who were randomized into two groups: simulation and lecture groups. PGY-II residents volunteered to conduct simulations and lectures. Knowledge evaluation was performed using pre- and post-tests, and self-evaluation of competence and behaviour-change and program evaluations were conducted using questionnaires. RESULTS: In both groups, knowledge test scores were found to improve significantly, and the score difference between pre- and post-tests in both the groups was not significant. Self-evaluation of competence and behaviour-change was found to be higher in the simulation group than the lecture group. The trainees in the simulation group valued the program and the PGY-II residents as teaching staff more than those in the lecture group. CONCLUSIONS: The combination of simulation-based learning and peer-assisted learning led by PGY-II residents is potentially more effective in improving the postgraduate education of PGY-I residents than the combination of lecture and peer-assisted learning.